A DECISION-MAKING FRAMEWORK FOR PRIORITIZING GREEN RETROFIT STRATEGIES IN CLINIC BUILDINGS USING AHP - Akhmad F. K. Khitam; Mochammad Qomaruddin; Ndaru Ahmad Rizqi; Lindawati; Zakhy Muhammad Luthfi; Mohammad Debby Rizani; Annisa' Carina; Supaphorn Akkapin (Jurnal Ilmiah Arsitektur, 2026)
Clinic buildings face challenges in improving environmental performance while maintaining operational efficiency and occupant comfort. This study aims to develop an Analytical Hierarchy Process (AHP)-based decision-making framework to prioritize green retrofit criteria for clinic buildings. The research was conducted by identifying relevant criteria and sub-criteria through a literature review and obtaining pairwise comparison judgments from 18 experts. The results indicate that the Economic criterion has the highest priority with a weight of 66.05%, followed by Health & User Comfort (18.96%), Technical (9.26%), and Environmental (5.74%) criteria. These findings suggest that financial feasibility is the primary consideration in green retrofit decision-making, although indoor environmental quality and occupant well-being remain important factors in healthcare facilities. The consistency test produced a Consistency Ratio (CR) of 0.0744, indicating acceptable judgment consistency. Furthermore, sensitivity analysis confirmed that the priority structure remained stable under various weight variation scenarios. Therefore, the proposed AHP framework can serve as a practical decision-support tool for prioritizing green retrofit initiatives in clinic buildings.